A consensus protocol for the management of medication-overuse headache: Evaluation in a multicentric, multinational study. (August 2014) - Tassorelli, C; Jensen, R; Allena, M; De Icco, R; Sances, G; Katsarava, Z; Lainez, M; Leston, JA; Fadic, R; Spadafora, S; Pagani, M; Nappi, G; et al.
Introduction: The management of medication-overuse headache (MOH) is often difficult and no specific guidelines are available as regards the most practical and effective approaches. In this study we defined and tested a consensus protocol for the management of MOH on a large population of patients distributed in different countries. Subjects and methods: The protocol was based on evidence from the literature and on consolidated expertise of the members of the consensus group. The study was conducted according to a multicentric interventional design with the enrolment of 376 MOH subjects in four centres from Europe and two centres in Latin America. The majority of patients were treated according to an outpatient detoxification programme. The post-detoxification follow-up lasted six months. Results: At the final evaluation, two-thirds of the subjects were no longer overusers and in 46.5% of subjects headache had reverted back to an episodic pattern of headache. When comparing the subjects who underwent out-patient detoxification vs those treated with in-patient detoxification, both regimens proved effective, although the drop-out rate was higher in the out-patient approach. Conclusions: The present findings support the effectiveness and usability of the proposed consensus protocol in different countries with different health care modalities.